2014
DOI: 10.1088/0004-637x/784/1/79
|View full text |Cite
|
Sign up to set email alerts
|

Young Star Clusters in the Circumnuclear Region of NGC 2110

Abstract: High-resolution observations in the near infrared show star clusters around the active galactic nucleus (AGN) of the Seyfert 1 NGC2110, along with a 90 x 35 pc bar of shocked gas material around its nucleus. These are seen for the first time in our imaging and gas kinematics of the central 100pc with the Keck OSIRIS instrument with adaptive optics. Each of these clusters is 2-3 times brighter than the Arches cluster close to the centre of the Milky Way. The core star formation rate (SFR) is 0.3 M⊙ yr -1 . The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…Comparing our [Fe ii] λ 1.2570 µm kinematic maps with those obtained by Durré & Mould (2014) for the same emission line, we find that they are consistent each to other, considering that the spatial orientation of the maps originally published is incorrect. Their maps are rotated by 90 • , to have the north-south direction along the y-axis (Durré, M., private communication).…”
Section: Gaseous Kinematicssupporting
confidence: 85%
See 2 more Smart Citations
“…Comparing our [Fe ii] λ 1.2570 µm kinematic maps with those obtained by Durré & Mould (2014) for the same emission line, we find that they are consistent each to other, considering that the spatial orientation of the maps originally published is incorrect. Their maps are rotated by 90 • , to have the north-south direction along the y-axis (Durré, M., private communication).…”
Section: Gaseous Kinematicssupporting
confidence: 85%
“…We concluded that the main H 2 excitation mechanism is heating of the gas by X-rays emitted from the AGN. Durré & Mould (2014) have also recently presented NIR IFS of the central region of NGC 2110 using J-band data obtained with the Keck I OSIRIS instrument and reported the detection of star clusters along with a 90×35 pc bar of shocked gas around the nucleus of NGC 2110. They derived a star formation rate of 0.3 M ⊙ yr −1 and argue that the star formation is triggered by the AGN feedback.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, young stellar populations revealed by PCA tomography may be associated with a more massive cluster or, perhaps, a combination of many clusters. For example, Durré & Mould (2014) detected four young stellar clusters encircling the AGN of the galaxy NGC 2110. Using IFU data with adaptive optics in the IR, they associated [Fe II] emissions with shocks caused by winds and/or SNR emerging from these clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are 3 instruments that meet the combined requirements of a telescope in the 8-10m class, adaptive optics and a near infra-red IFU; these are SINFONI on VLT (Eisenhauer et al 2003), NIFS on Gemini North (McGregor et al 2003) and OSIRIS on Keck I (Larkin et al 2006). This paper is the second on the Mould et al (2012) galaxies, the first was on NGC 2110 (Durré & Mould 2014), which showed young, massive star clusters embedded in a disk of shocked gas from stellar winds which feed the black hole; the star formation rate is 0.3 M yr −1 , easily sufficient to produce the clusters on a million year timescale. The gas kinematics produced an estimate for the enclosed central mass of 3.2 − 4.2 × 10 8 M .…”
Section: Our Programmentioning
confidence: 99%